Challenges and strategies to enhance Online Remote Teaching and Learning by tertiary institution educators: a literature review - Mazlan, Ahmad Farit; Mohamad, Maslawati; Reesha, Aishath; Kassim, Rosnani; Othman, Zarina; Kummin, Saadiah (Scientific Research Publishing, 2021)
In 2019, Covid-19 has been declared as a global pandemic. Online remote teaching and learning is the most practical solution to continue teaching and learning particularly at tertiary institutions. There is a drastic change from face-to-face teaching and learning to a fully online teaching and learning environment. Tertiary institutions need to ensure that they consolidate the curriculum and adjust it in accordance with online teaching and learning. In accordance with the new normal in teaching and learning, educators must adapt to new and creative strategies to engage students during online remote teaching and learning. This paper is a literature review on 1) the challenges faced by tertiary institution educators in online remote teaching and learning and 2) strategies that they used to carry out their teaching during this Covid-19 outbreak in order to overcome those challenges.